2001
DOI: 10.1002/cjg2.182
|View full text |Cite
|
Sign up to set email alerts
|

Recent Horizontal Movement And Deformation in The Northeast Margin of Qinghai–Xizang Block

Abstract: Making use of GPS observational data in area of the northeast margin of Qinghai–Xizang block in the years 1993 and 1999, the distribution figures of velocity field and apparent strain field of crustal horizointal movement of this area are given, and the method of directly solving the parameters of block rotation and deformation from displacement observation is presented, so the characteristics of tectonic block motion and deformation in this area are studied preliminarily. The results show that: (1) This area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…[4,5] The M-A constituents are in a hard brittle phase and can easily cause stress concentration and become potential crack sources, leading to serious deterioration of the impact toughness of ICR CGHAZ. [7,8] However, Jiang et al [9] found that Nb-V-Ti high-strength low-carbon bainitic steel does not exhibit local embrittlement in ICR CGHAZ, which indicates that the local embrittlement region is SR CGHAZ. Inhomogeneous grain size and large long-chain M-A constituents lead to decreased toughness.…”
mentioning
confidence: 98%
“…[4,5] The M-A constituents are in a hard brittle phase and can easily cause stress concentration and become potential crack sources, leading to serious deterioration of the impact toughness of ICR CGHAZ. [7,8] However, Jiang et al [9] found that Nb-V-Ti high-strength low-carbon bainitic steel does not exhibit local embrittlement in ICR CGHAZ, which indicates that the local embrittlement region is SR CGHAZ. Inhomogeneous grain size and large long-chain M-A constituents lead to decreased toughness.…”
mentioning
confidence: 98%